6t+3(5+-4)=12(12t-5)

Simple and best practice solution for 6t+3(5+-4)=12(12t-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6t+3(5+-4)=12(12t-5) equation:



6t+3(5+-4)=12(12t-5)
We move all terms to the left:
6t+3(5+-4)-(12(12t-5))=0
We add all the numbers together, and all the variables
6t-(12(12t-5))+31=0
We calculate terms in parentheses: -(12(12t-5)), so:
12(12t-5)
We multiply parentheses
144t-60
Back to the equation:
-(144t-60)
We get rid of parentheses
6t-144t+60+31=0
We add all the numbers together, and all the variables
-138t+91=0
We move all terms containing t to the left, all other terms to the right
-138t=-91
t=-91/-138
t=91/138

See similar equations:

| 10-5x+30=50 | | (1/2x)+3=1/2 | | 7x-10=-2x+8+9 | | 8x−5x+7=572−565 | | (4x-3)+(2x+1)=112 | | 9x+6=6(x+2)+3x | | 11*x=x | | 10-2r=-6* | | (4x-3)(2x+1)=112 | | 5(r+9)=-58 | | X+12=3x+10x-20X | | -13-(44)=x/7 | | 3(5n-4)=8+2 | | 21/15=n/5 | | -4x=369 | | 192=8*x*4 | | 2x/51-3=5x/17 | | -4k+8k=k+5-2+15 | | 18-2x=-2-7x | | 5x-6=5x+3-3x | | 6(6v+5)-5=1+6v | | -2(2x-7)=4x-14 | | 10y-7y-15=45.24 | | 8x−3−5x+6=9 | | 5x-(x-3)+6=17 | | 1565+5x=1640-9x | | `-3x=27` | | 2x+23=x+21 | | 10+12x=-158 | | 11j+9=-2j+45 | | 7x=-44 | | 28-3(2w-1)=5w-3(5+w) |

Equations solver categories